Pengembangan Modul Sistem Pencernaan Manusia dengan Mengintegrasikan Ayat-Ayat Al-Qur’an - Sa’adah Rahmayani; Alwan Mahsul; Najah Sholehah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The purpose of this study is to develop a module and investigate the feasibility of an integrated module of Al-Qur'an verses on digestive materials for class VIII MT students. This research uses a 4D model R&D method that consists of a definition phase, a design phase, a development phase, and a dissemination phase. A data collection tool in the form of validation sheets and student surveys. The questionnaires used are an expert validation questionnaire to assess the feasibility of the product and a student questionnaire to confirm the effectiveness and practicality of the product. The value of validity by media expert lecturers is 67.05%. Lecturer of material experts by 80%. The practicality level of the student response module for class VIII MTs is 80.69%, the practicality data for class VIII Putri is 81.66% and the practicality data for Integrated Science teachers reaches 100%. The result of this study is an edit of the Human Digestive System Integration Module, and the Quranic verses of the Madrasah Tsanawiyah School are useful and practical for learning.